2017
DOI: 10.1073/pnas.1701747114
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an orthomyxovirus matrix protein reveals mechanisms for self-polymerization and membrane association

Abstract: Many enveloped viruses encode a matrix protein. In the influenza A virus, the matrix protein M1 polymerizes into a rigid protein layer underneath the viral envelope to help enforce the shape and structural integrity of intact viruses. The influenza virus M1 is also known to mediate virus budding as well as the nuclear export of the viral nucleocapsids and their subsequent packaging into nascent viral particles. Despite extensive studies on the influenza A virus M1 (FLUA-M1), only crystal structures of its N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Furthermore, protein–protein and protein– lipid interactions occurring during membrane binding of M1 are accompanied by a moderate but significant alteration in secondary structure. These findings support a model of M1–M1 interactions that we and others have discussed [21, 32, 38], according to which binding of M1 to the PM (mediated by the N-terminal domain) could affect the structure or the chain dynamics of the protein (specifically of the C-terminal domain), thus exposing or stabilizing the interfaces for M1 self-association [32] and, possibly, vRNP binding [21].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, protein–protein and protein– lipid interactions occurring during membrane binding of M1 are accompanied by a moderate but significant alteration in secondary structure. These findings support a model of M1–M1 interactions that we and others have discussed [21, 32, 38], according to which binding of M1 to the PM (mediated by the N-terminal domain) could affect the structure or the chain dynamics of the protein (specifically of the C-terminal domain), thus exposing or stabilizing the interfaces for M1 self-association [32] and, possibly, vRNP binding [21].…”
Section: Discussionsupporting
confidence: 86%
“…While crystal structures of the relatively compact M1 N-terminal domain have been solved at pH 4.0 and 7.0, both the structure and the exact orientation of the more flexible and disordered C-terminal domain within the full-length protein remain unclear [33-37]. A recently published crystal structure of the matrix protein from another orthomyxovirus, the infectious salmon anaemia virus (ISAV), provides first clues on the 3D structure of full-length IAV M1 [38].…”
Section: Introductionmentioning
confidence: 99%
“…A trans-interface between NTD and CTD is present within the crystal packing of the ISAV matrix protein (Extended data Fig. 3d) 13 .…”
Section: Influenza a Virus Causes Millions Of Severe Illnesses Duringmentioning
confidence: 99%
“…There are no structures available for the CTD of M1. A structure of the full-length matrix protein is available from an orthomyxovirus Infectious Salmon Anemia Virus (ISAV), however substantial divergence (18% sequence identity) between ISAV and IAV matrix proteins makes it unclear how relevant the ISAV matrix protein structure is to IAV M1 13 . Classical electron microscopy suggests that M1 forms a helical arrangement of fibers in both filamentous 14,15 and spherical virions 16 , but how M1 oligomerizes and is arranged to form the viral endoskeleton is unknown.…”
Section: Influenza a Virus Causes Millions Of Severe Illnesses Duringmentioning
confidence: 99%
“…Although this phenomenon was noted previously [23], the reason for this is still not understood. The M1 protein interacts with the HA and NA glycoproteins during assembly of the virus particle [37], therefore the co-assortment of these three segments might reflect specific structural complementation in the proteins they encode, but further investigations are required for clarity. The surface glycoproteins HA and NA are constantly exposed to the host immune system and Rauff et al [23] previously reported that sub-lineage I mutates at the higher rate of 7.7 x 10 -3 nucleotide substitutions per site per year compared to 4.05 x 10 -3 for sub-lineage II, attributed to vaccine pressure.…”
Section: H6n2 Reassortment Antigenic Diversity and Evolutionmentioning
confidence: 99%